Creation of a Project Portfolio for a Construction Company by Using Lean Six Sigma Principles : Change Management, as part of Clarifying the Case Company’s Strategy - Partanen, Okko (My University, 2023)
Project Portfolio Management (PPM) is an important tool for an industrial companies to achieve a competitive advantage. Companies in the Construction Industry, especially in Infrastructure construction, where the majority of companies are small or medium-sized, generally do not have the capacity or knowledge for the strategic selection of projects as part of the company's future strategy, as there is a dearth of knowledge on project level PPM and Lean Six Sigma. This causes companies to blindly bid on different projects, hoping for a good outcome, as the selection of projects is not based on knowledge or facts. This causes companies to offer projects, that are negatively correlated to their own strategy, which in the long run will worsen the company's ability to generate prof-it, as projects do not create synergies between the companies' different business areas. In the ever-tightening competition in the market, where the cheapest offer invariably wins, the company must consider the Lean Six Sigma -mentality in its production, where it strives to optimize its own processes to achieve a situation, where it produces more added value with its processes, more efficiently and at lower costs. Only by learning from its own production can company achieve a competitive edge in a market. The methodology of the research has been based on the Case Company's interviews and internal docu-ments, on which the analysis has been formed by using the literature of the field. This study focuses on analyzing the production processes of an influential infrastructure construction company in Finland, aiming to optimize the company's strategy-, production-, and bidding processes, by developing a Project Portfolio Management -tool, so that the company has a better competitive position in future.

Project Portfolio Management (PPM) on tärkeä työkalu teollisuusyrityksille kilpailuedun saavuttamisessa. Erityisesti infra-alaan erikoistuneista rakennusalan yrityksistä suurin osa on pieniä tai keskisuuria. Tämän takia yrityksillä ei yleisesti ottaen ole kapasiteettia, tietoa tai projektitason PPM- ja Lean Six Sigma -osaamista, strategisesta projektien valinnasta osana yhtiön strategisia tavoitteita. Infrarakentamisen parissa toimivat yritykset perustavat tarjouslaskentansa eri rakennusprojekteissa arvioihin, toivoen hyvää lopputulosta. Hankkeiden tarjouslaskenta perustuu tällöin arvailuun, eikä tietoon tai tosiasioihin. Tämä saa yritykset tarjoamaan omaan strategiaansa negatiivisesti vaikuttavia projekteja, jotka eivät luo synergiaetuja yritysten eri liiketoiminta-alueiden välille ja pitkällä aikavälillä heikentävät yrityksen kannattavuutta. Alalla vallitsevan kilpailun jatkuvasti kiristyessä, jossa halvin tarjous poikkeuksetta voittaa, tulee yrityksen huomioida Lean Six Sigma -mentaliteetti tuotannossaan. Yrityksen tulee pyrkiä optimoimaan omia prosessejaan saavuttaakseen tilanteen, jossa se tuottaa enemmän lisäarvoa resursseillaan tehokkaammin ja edullisemmin. Vain omasta tuotannostaan oppimalla yritys voi saavuttaa merkittävää kilpailuetua markkinoilla. Tämä tutkimus keskittyy Suomessa toimivan infrarakentamiseen erikoistuneen yrityksen tuotantoprosessien analysointiin; tavoitteena optimoida yrityksen strategia-, tuotanto- ja tarjousprosesseja. Tutkimuksen lopputuotteena kehitettiin Project Portfolio Management -työkalu, jota hyödyntämällä yrityksellä on mahdollisuus parempaan kilpailuasemaan tulevaisuudessa. Tutkimuksen metodologia on perustunut Case Yrityksen haastatteluihin sekä sisäisiin asiakirjoihin, joiden perusteella analyysi on muodostettu alan kirjallisuutta hyödyntäen.
Keywords: organisations (systems); leadership (activity); project leadership; development (active); corporate strategies; construction industry; portfolios; quality management; fi=Tuotantotalous (tekniikka)|en=Industrial Management and Engineering|; Master's Programme in Industrial Systems Analytics